Обряд кремації у стародавнього населення території України (V тис. до н. е. — І тис. н. е.) - Отрощенко, В.В.; Моця, О.П. (Археологія, 1989)
На території України обряд кремації з’являється ще в епоху неоліту, зокрема у носіїв культури лінійно-стрічкової кераміки. Його остання фаза — це перші віки існування Давньоруської держави. У таких регіонах, як Волинь, Закарпаття, Верхній Дністер, Київське Подніпров’я, обряд кремації використовувався постійно протягом тисячоліть. Його вивчення дає можливість зробити ряд спостережень з точки зору історії культури, етнічних процесів та ідеологічних уявлень. В статье дается обзор случаев проявления обряда трупосожжения у племен различных археологических культур на территории Украины. Выясняется, что практикование кремаций на различных территориях имеет более или менее устойчивые традиции, восходящие к эпохам неолита и энеолита. В таких регионах как Волынь, Закарпатье, Верхнее Поднестровье и Киевское Поднепровье этот обряд бытовал на протяжении тысячелетий у носителей различных археологических культур. Напротив, в степной полосе территории Украины обряд кремации фиксируется спорадически (срубная, Черняховская, некрополи греческих городов). Чужд обряд кремации кочевым обществам, а наиболее практикуем земледельческими. В отдельных регионах (Левобережная Лесостепь, Среднее Поднестровье) обряд кремации распространялся периодически, в зависимости от активизации лесостепных племен (фракийцы, славяне), и исчезал вследствие натиска степняков, скифов, в частности. Здесь особенно заметно, что за динамикой смены погребальных обрядов стояли политические и экономические события большого исторического значения.
Рассматриваются взгляды на причины появления обряда кремации и его место в системе ранних форм религии (погребальный культ, культ предков, культ жилища и домашнего очага). Указывается на определенную связь обряда кремации с развитием анимистических представлений у древнего населения территории Украины. Особо оговорена глубокая древность практики помещения праха умершего в погребальную урну. Отмечена перспективность изучения конкретных форм обряда кремации в их историческом развитии. The paper presents a review of cases of cremation rite in the tribes of various archaeological cultures in the territory of the Ukraine. It is found out that cremation in various territories possesses more or less stable traditions going back to the Neolithic and Eneolithic epochs. This ritual existed for millennia in the carriers of different archaeological cultures in the territories of Volyn, Transcarpathia, Upper Dniester and Kiev Dnieper Areas. On the contrary, in the steppe belt of the Ukraine territory the ritual of cremation is fixed sporadically (frame, Chernyakhovian cultures, necropolises of Greek towns). The rite was alien to nomadic societies and was most often used by agricultural ones. In certain regions (the Left Bank Forest-Steppe, Middle-Dniester Area) the cremation rite existed periodically depending on the activization of the Forest-Steppe tribes (Francians, Slavs) and disappeared as a result of the onslaught of steppe tribes, Scythians, in particular. It is especially noticeable that the dynamics of change of the funeral rite was underlain by political and economical events of great historical value.
The views on the causes which induced cremation rite and the place the latter occupied in the system of early forms of religion (cult of funerals, cult of ancestors, cult of the dwelling and home) are considered. Cremation rite is found to be somewhat related to the development of animistic ideas in the ancient population of the Ukrainian territory. Deep antiquity of the practice to place ashes to the urn is mentioned apart. The study of concrete forms of cremation in their historical development is stated to be promising.